2013
DOI: 10.1016/j.pain.2013.04.030
|View full text |Cite
|
Sign up to set email alerts
|

TRPA1 insensitivity of human sural nerve axons after exposure to lidocaine

Abstract: TRPA1 is an ion channel of the TRP family that is expressed in some sensory neurons. TRPA1 activity provokes sensory symptoms of peripheral neuropathy, such as pain and paraesthesia. We have used a grease gap method to record axonal membrane potential and evoked compound action potentials (ECAPs) in vitro from human sural nerves and studied the effects of mustard oil (MO), a selective activator of TRPA1. Surprisingly, we failed to demonstrate any depolarizing response to MO (50, 250 μM) in any human sural nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…In the sciatic nerve, FKN-induced production of ROS from CX3CR1-expressing macrophages in the vicinity of sensory axons could result in a pronociceptive effect through the activation of TRPA1 receptors that are functionally located at axonal level (39)(40)(41). Thus, we demonstrated that 2 TRPA1 antagonists, AP-18 and A967079, repeatedly administered during the first VCR cycle, significantly prevented the development of VCR-induced allodynia by approximately 20% (Supplemental Figure 9).…”
Section: Figurementioning
confidence: 65%
See 1 more Smart Citation
“…In the sciatic nerve, FKN-induced production of ROS from CX3CR1-expressing macrophages in the vicinity of sensory axons could result in a pronociceptive effect through the activation of TRPA1 receptors that are functionally located at axonal level (39)(40)(41). Thus, we demonstrated that 2 TRPA1 antagonists, AP-18 and A967079, repeatedly administered during the first VCR cycle, significantly prevented the development of VCR-induced allodynia by approximately 20% (Supplemental Figure 9).…”
Section: Figurementioning
confidence: 65%
“…Surprisingly, MO loses efficacy in human isolated sural nerves, but this is very likely due to nerve exposure to local anesthetic during surgery. Indeed, lidocaine desensitizes murine TRPA1 channel, thereby suggesting that this mechanism, in combination with sodium channel blockade, underlies lidocaine efficacy in treating neuropathic pain (39). This is a plausible suggestion, as TRPA1-immunoreactive fibers are expressed in human peripheral nerves (41).…”
Section: Animalsmentioning
confidence: 99%
“…A-delta fibres in the rat sciatic nerve had half maximum blocking concentration of lidocaine of 0.32 mmol/L which was much lower than for C-fibres (0.8 mmol/L) (Huang et al, 1997)possibly linked to Na V 1.6 expression in A-delta fibres compared to TTXr Na V 1.8 (Kistner et al, 2010) in Cfibres. Lidocaine may also mediate effects via other relevant membrane components, such as K + -channels (Brau et al, 1995;Nayak et al, 2009), Na + /K + pumps (Almotrefi et al, 1999;Zeng et al, 1999;Kutchai et al, 2000), Ca 2+ -channels (Guo et al, 1991), TRPA1 Docherty et al, 2013) and TRPV1 (Leffler et al, 2008). Lidocaine may also mediate effects via other relevant membrane components, such as K + -channels (Brau et al, 1995;Nayak et al, 2009), Na + /K + pumps (Almotrefi et al, 1999;Zeng et al, 1999;Kutchai et al, 2000), Ca 2+ -channels (Guo et al, 1991), TRPA1 Docherty et al, 2013) and TRPV1 (Leffler et al, 2008).…”
Section: Sensory Submodalities Differentially Sensitive To Lidocainementioning
confidence: 99%
“…This may reflect the prolonged analgesic effects sometimes seen that outlast the expected presence of lidocaine in the tissue [163].…”
Section: The Rationale For Ivlt In the Management Of Painmentioning
confidence: 99%